Mean platelet volume/platelet count ratio in colorectal cancer: a retrospective clinical study - Yang-Yang Wu; Xuan Zhang; Yuan-Yuan Qin; Jin-Qiu Qin; Fa-Quan Lin (BMC Cancer, 2019)
Abstract Background Mean platelet volume (MPV) is a marker of platelet activation. MPV and platelet count (PC) are negatively correlated, and their ratio (MPV/PC) is informative for the diagnosis of malignant tumors. However, the relationship between MPV/PC and colorectal cancer is unclear. This retrospective clinical study aimed to evaluate the diagnostic value of MPV/PC in colorectal cancer. Methods Hematological examinations were performed at initial diagnosis in patients with colorectal cancer (n = 186) or adenomatous polyp (n = 132) and healthy controls (n = 108). Hematological parameters evaluated included white blood cells, red blood cells, hemoglobin, neutrophils, lymphocytes, monocytes, PC, and MPV. Statistical analyses included Student’s t-test, one-way ANOVA or Kruskal-Wallis H test, chi-square tests, Spearman’s correlation test and receiver operating characteristic (ROC). ROC curve was used to evaluate the diagnostic values of MPV and MPV/PC in colorectal cancer. Results Among these groups, MPV was significantly lower in colorectal cancer than in adenomatous polyp (p = 0.002) and healthy controls (p < 0.001) but did not significantly differ between adenomatous polyp and healthy controls (p = 0.210). MPV/PC was lower in colorectal cancer compared with adenomatous polyp and healthy controls (p < 0.001) and in adenomatous polyp compared with healthy controls (p = 0.010). MPV did not significantly differ among colorectal cancer subgroups, while MPV/PC significantly differed between TNM stages and the presence/absence of lymph node metastasis. MPV/PC was negatively correlated with the neutrophil to lymphocyte ratio(NLR) (p = 0.002) and platelet to lymphocyte ratio(PLR) concentration (p < 0.001). In the differential diagnosis between colorectal cancer and adenomatous polyp, MPV/PC produced a larger ROC curve than MPV, NLR or PLR alone. Using MPV/PC to distinguish between colorectal cancer and controls produced a larger AUC than using MPV or NLR alone. Conclusions MPV/PC may be useful for the diagnosis of colorectal cancer. However, further studies are warranted to include additional regions and more data, to assess the utility of MPV/PC as a novel diagnostic screening tool for colorectal cancer.